2022
DOI: 10.3390/biology11030404
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Solutions for Agriculture: Foliar Application of Wood Distillate Alone and in Combination with Other Plant-Derived Corroborants Results in Different Effects on Lettuce (Lactuca Sativa L.)

Abstract: Bio-stimulants are showing growing success and are gradually replacing synthetic fertilizers in agriculture. Wood distillate (WD), also known as wood vinegar or pyroligneous acid, is a by-product of biomass pyrolysis and is increasingly used as a bio-stimulant for crop production. This study investigated whether weekly foliar applications of 0.25% and 0.50% WD have a differential effect on the chlorophyll and sugar content as well as biomass production in lettuce (Lactuca sativa L.). Moreover, the additional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
6
27
0
Order By: Relevance
“…In our study, the remarkable increase in starch (+45.9%) in WD‐treated plants suggests a very beneficial effect of WD on chickpea. This result is consistent with the doubled starch content found in 0.25% and 0.50% WD‐treated lettuce plants (Fedeli et al, 2022). Similarly, also Jee and Cho (2005) reported that WD at concentrations within 0.5% increased the starch content in the roots of the orchid Neofinetia falcata Thunb.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, the remarkable increase in starch (+45.9%) in WD‐treated plants suggests a very beneficial effect of WD on chickpea. This result is consistent with the doubled starch content found in 0.25% and 0.50% WD‐treated lettuce plants (Fedeli et al, 2022). Similarly, also Jee and Cho (2005) reported that WD at concentrations within 0.5% increased the starch content in the roots of the orchid Neofinetia falcata Thunb.…”
Section: Discussionsupporting
confidence: 91%
“…Although not statistically significant, plant biomass also increased (+37%) following the application of 0.25% WD. This trend is consistent with the results reported in the literature for several crop plants: lettuce ( Lactuca sativa L.) +39% (Vannini et al, 2021), +49% (Fedeli et al, 2022), +42% (Mu et al, 2006), tomato ( Solanum lycopersicum L.) +27% (Mungkunkamchao et al, 2013), rice ( Orzya sativa L.) +30% (Zulkarami et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…WD is rich in antioxidants, such as polyphenols [15,17,37], and is effectively used to increase both the chlorophyll content and biomass of crop plants, as found in some recent studies [16,[38][39][40][41]. Although the mechanisms behind its effectiveness are still in need of investigation, it has been suggested that this stimulant effect on plant productivity may be due to the action of antioxidant molecules on cell division [16], in response to the activation of specific transcription genes, as previously observed by Tanase et al [42,43].…”
Section: Discussionmentioning
confidence: 99%